The Pembuatan Eco-Enzyme Dari Limbah Organik Buah Dan Sayur Sebagai Pupuk Organik Cair : Studi Kasus Pasar Raya Medan Mega Trade Centre (MMTC) - Clarissa Oktoferin Sinaga; Muhammad Najmul Fahmi; Shika Andari; Meilinda Suriani Harefa; Syukri Hidayat (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Eco-enzymes are liquid products resulting from the fermentation of organic wastes such as fruit and vegetable wastes, sugar, and water. The aim of this study is to investigate the potential of eco-enzymes as liquid organic fertilizers using organic waste from orange and pineapple peels. In the experimental design, he used a completely randomized design with three replicates of three organic waste compositions. The treatments used are pineapple peel, orange peel, and a mixture of pineapple and orange peel. Ecoenzyme is prepared by mixing organic waste with water and molasses in a ratio of 10: 3: 1 and fermenting it for 30, 60 and 90 days. The results showed that the composition of pineapple and orange peel produced an eco-enzyme solution with the highest nitrogen content, highest amylase enzyme activity, and highest acidic pH. The color of eco-enzyme varies from light brown to dark brown, and the resulting sour aroma indicates that the fermentation process is progressing smoothly.